2015
DOI: 10.1136/gutjnl-2015-310139
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of endoscopic surveillance recommendations in organised colorectal cancer screening programmes based on the faecal immunochemical test

Abstract: In organised screening programmes, a high rate of inappropriate recommendations for patients with low risk or no adenomas occurs, affecting the demand for endoscopic surveillance by a third.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 42 publications
1
31
0
2
Order By: Relevance
“…According to such documents, appropriate surveillance indications may be given only after a high‐quality baseline colonoscopy. However, in clinical practice, post‐polypectomy surveillance recommendations could be made by clinicians who may not be very familiar with colonoscopy quality metrics, especially in the setting of organized screening programs . In addition, position statements addressing the quality of colonoscopy are generally skewed toward the concern of detection rather than surveillance, as adenoma detection rate and withdrawal time have been associated with the risk of post‐colonoscopy interval cancer, irrespective of post‐polypectomy surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…According to such documents, appropriate surveillance indications may be given only after a high‐quality baseline colonoscopy. However, in clinical practice, post‐polypectomy surveillance recommendations could be made by clinicians who may not be very familiar with colonoscopy quality metrics, especially in the setting of organized screening programs . In addition, position statements addressing the quality of colonoscopy are generally skewed toward the concern of detection rather than surveillance, as adenoma detection rate and withdrawal time have been associated with the risk of post‐colonoscopy interval cancer, irrespective of post‐polypectomy surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Early colonoscopies were more frequent in patients with an original surveillance interval of greater than 3 years. An Italian study found increased frequency of surveillance resulted in about 6700 more colonoscopies than expected, accounting for more than one‐third of all of colonoscopies recommended in 2013 21 . We have previously reported that adherence to national guidelines could reduce the annual number of post‐polypectomy colonoscopies by 26% 14 …”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that the majority of interval cancers are diagnosed between 2 and 3 years after the baseline colonoscopy [18] and are due to missed and incompletely resected lesions [21]. However, this recommendation comes with a risk of overuse with this approach, especially in FIT-based screening programs where the proportion of patients that fit in this high-risk group as defined by the EU guidelines is around 6% [42]. Repeating these base-line clearing colonoscopies could form an extra burden for the already overloaded screening programs.…”
Section: Intermediate Versus High-risk Groupmentioning
confidence: 96%
“…This phenomenon may be typically observed in opportunistic CRC screening programs, where utilization of services depends on the initiative of individuals and on individual encounters with health care providers. However, a recent study from an organized FIT-based screening program in Italy showed an average rate of inappropriate surveillance procedures of 37%, with rates as high as 67% in patients with low-risk adenomas [42]. In organized screening programs, invitations for screening as well as surveillance could both be issued from centralized registers.…”
Section: Adequacy and Adherence To Guidelinesmentioning
confidence: 98%